2019
DOI: 10.1126/sciadv.aax0648
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquid–based click-ionogels

Abstract: Gels that are freeze-resistant and heat-resistant and have high ultimate tensile strength are desirable in practical applications owing to their potential in designing flexible energy storage devices, actuators, and sensors. Here, a simple method for fabricating ionic liquid (IL)–based click-ionogels using thiol-ene click chemistry under mild condition is reported. These click-ionogels continue to exhibit excellent mechanical properties and resilience after 10,000 fatigue cycles. Moreover, due to several uniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
247
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(251 citation statements)
references
References 41 publications
3
247
0
1
Order By: Relevance
“…At H 2 O levels greater than 10 wt %, such as 16 wt %, the protons undergo a significant upfield shift ( Figure 2B), which is attributed to the formation of H bonds between H 2 O molecules and ions. 18,20,21 Strongly polar O-H in H 2 O is inclined to cause the lone pair of electrons of N (nitrogen in the imidazole ring) to be biased toward H of H 2 O, thereby forming the H bond (in the form of hydrated ions). This process leads to the increase in electron cloud density of protons in the imidazole ring and the chemical shift moving upfield.…”
Section: Dynamic Gel With Tunable Turing Microstructures and Hydrogenmentioning
confidence: 99%
“…At H 2 O levels greater than 10 wt %, such as 16 wt %, the protons undergo a significant upfield shift ( Figure 2B), which is attributed to the formation of H bonds between H 2 O molecules and ions. 18,20,21 Strongly polar O-H in H 2 O is inclined to cause the lone pair of electrons of N (nitrogen in the imidazole ring) to be biased toward H of H 2 O, thereby forming the H bond (in the form of hydrated ions). This process leads to the increase in electron cloud density of protons in the imidazole ring and the chemical shift moving upfield.…”
Section: Dynamic Gel With Tunable Turing Microstructures and Hydrogenmentioning
confidence: 99%
“…Recently, Kim et al 38 reported an ionic mechanoreceptor skin which composed of hydrogen-bonded [EMIM][TFSI] ion pairs on the surface of silica microstructures embedded into thermoplastic polyurethane elastomeric matrix, exhibiting a higher fraction strain of 800%, but the ionic conductivity of the ionogel (0.007 S m À1 ) is much lower than that of our ionogel. Yan et al 39 further reported an ionogel with high ultimate tensile strain of 1390% and ionic conductivity of about 0.8 S m À1 at 25 C by a simple method using thiol-ene click chemistry under mild condition. Overall, our PAMPS-based DN ionogel exhibits outstanding ionic conductivity while maintaining relatively good mechanical strength.…”
Section: Resultsmentioning
confidence: 99%
“…However, the nature of covalently cross-linked PAAm hydrogel makes the absence of self-healing in this touch pad. Recently, transparent and conductive ionogels comprised of ionic liquids and polymers have been used as ionoskins to sense touch position, [22] force, [23] and monitor human movements, [24] with the biggest merit of no volatilization. [24] However, due to the absence of functional groups for bonding, these ionogels are nonadhesive, therefore, there is a need to be fixed on target surfaces with the help of tapes or glues.…”
Section: Doi: 101002/adma202004290mentioning
confidence: 99%